Peranan Inovasi Dan Komunikasi Marketing Terpadu Dalam Keputusan Memilih Perguruan Tinggi (Kasus ITL Trisakti) - Ratna Suminar; Sri Wahyuni (Institut Transportasi dan Logistik Trisakti, 2021)
This study was conducted in ITL Trisakti Jakarta in order to analyze the effect of the application of IMC and Innovation towards Purchase Intention of university selection. The study was conducted using quantitative-hypothesis testing research. The validity and reliability testing research was conducted using SPSS program, while the data was analysed using Structural Equation Modelling (SEM). The result of the study shows there is not significant influence of innovation to the respondents’ decision making on university selection. However, there is a significant influence of the IMC strategies applied to the respondents’ decision making. Furthermore, respondents’ quality perception, as the intervening variable, shows direct and significant influence to the respondents’ decision making on university selection. Specifically, internet and marketing evenst have big contribution to the application of IMC in ITL Trisakti, despite; Advertising and Personal Selling show the least. Therefore, ITL Trisakti is expected to develop the marketing strategy in order to get the best result.